Territories of literary history: the shifting boundaries of Francophone literature in Canada - Chapman, Rosemary (Laurentian University, Ontario, 2013)
The writing of literary history opens up a range of questions about territory and boundaries. While recognising the energising role of Quebec nationalism in the emergence and affirmation of Québécois literature in the second half of the Twentieth Century, it is important to recognize the effects of such a national(ist) narrative on the shape of literary history, on its focus, its inclusions and exclusions. No single narrative can account for the complex literary history of Francophone literature in Canada. The enduring impact of Canada’s colonial past on the indigenous population, on the two settler communities and on subsequent waves of inward and outward migration has resulted in a literary and cultural life which needs to be viewed from a range of different perspectives. This article will begin to explore how notions of territory might contribute to a more flexible and inclusive understanding of the literary histories of Francophone literature in Canada.